Adiponectin retards the progression of diabetic nephropathy in db/db mice by counteracting angiotensin II. Issue 2 (10th February 2014) - Guo, Xiaohua; Zhou, Guangyu; Guo, Meizi; Cheung, Alfred K; Huang, Yufeng; Beddhu, Srinivasan
Abstract Adiponectin is a multifunctional adipokine with insulin‐sensitizing, anti‐inflammatory, and vasoprotective properties. Epidemiology studies have, however, shown that high levels of serum adiponectin are associated with kidney disease progression. We, therefore, examined the effect of adiponectin administration on the progression of glomerulosclerosis in the obese diabetic (db/db) mouse, a model of type II diabetes. Recombinant human adiponectin was administered intraperitoneally at a dose of 30 or 150 μg per day from weeks 18 to 20. Rosiglitazone administered by gavage at 20 mg/kg body weight (BW) daily served as a therapeutic control. Untreated uninephrectomized db/db mice developed progressive albuminuria and glomerular matrix expansion, associated with increased expression of transforming growth factor beta 1 (TGFβ1), plasminogen activator inhibitor type 1 (PAI‐1), collagen I (Col I), and fibronectin (FN). Treatment with adiponectin at either dose reduced the increases in albuminuria and markers of renal fibrosis seen in db/db mice, without affecting BW and blood glucose. Renal expressions of tumor necrosis factor‐α (TNF‐α) and monocyte‐chemoattractant protein‐1 (MCP‐1) and urinary TNF‐α levels, the markers of renal inflammation, were increased in diabetic mice, whereas adiponectin treatment significantly reduced the levels of these markers. Furthermore, adiponectin obliterated the stimulatory effects of angiotensin II (Ang II), but not the total effect of TGFβ1, on the mRNA expression of PAI‐1, Col I, and FN by cultured glomerular mesangial cells. These observations suggest that adiponectin treatment reduces glomerulosclerosis resulting from type II diabetes probably through its anti‐inflammatory and angiotensin–antagonistic effects. Thus, adiponectin has therapeutic implications in the prevention of progression of diabetic nephropathy.